(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Distal radius fractures are among the most common upper extremity fractures and the second most common overall fracture in Orthopaedics and trauma. Deciding between non-operative or operative management depends on the patient factors, fracture pattern, displacement and the treating orthopaedic surgeon. The objective of our study was to assess the functional and radiological outcome in lower end radius fractures, treated or untreated at the end of 1 year follow up. Material and methods: Our study was a prospective hospital-based study during the period January 2021 and December 2022. All closed lower end radius fractures meeting the inclusion/exclusion criteria and willing for follow up assessments were included in the study. Study subjects were divided into 2 groups- Treated/Operated group & Untreated/Non-operated group of patients. All patients were followed up at 6 weeks, 3 months and 1 year post injury and their functional and radiological outcomes were assessed and compared between the 2 groups. Results: A total of 100 patients were included in the study who met the required inclusion/exclusion criteria. There was 3 times more incidence among males as compared to females. Mean age was 45.1 yrs. High energy injuries were more frequent in younger patients. Frykman type I>II>VIII were the common type of fracture pattern noted in our study. In our study of 100 patients, 41 patients did not undergo operative intervention and 59 patients underwent some form of operative procedure. We observed that the acceptance of operative intervention was more in younger patients. Based on radiological criteria, 72 patients had excellent radiological outcome overall, out of which 49 patients belonged to operative group and only 23 patients belonged to non-operative group. There was only marginally better PRWE – Patient Rated Wrist Evaluation scores in operated group of patients as compared to non-operated group. Conclusion: Lower end radius fractures have a bimodal age of incidence with a peak in younger patients usually associated with high velocity injuries, and in elderly patients usually secondary to low velocity injuries mostly due to falls. Based on Frykman classification, the more severe the injury there is more acceptance of operative intervention. Operative intervention results in better radiological outcome at 1 year.